Effect of rootstock and nitrogen fertilizer on growth and yield in watermelon. Issue 6 (2nd November 2019) - Suchoff, David H; Schultheis, Jonathan R.; Gunter, Christopher C.; Hassell, Richard L.; Louws, Frank J.
ABSTRACT: Herbaceous grafting can be used to manage numerous soilborne pathogens in cucurbits. Rootstocks have been reported to increase the growth of the scion possibly due to more efficient use of nitrogen compared with non-grafted plants. The first objective of this study was to determine if the commercial rootstocks 'Strongtosa', 'Carnivor', or 'Macis' improve growth and production of the watermelon 'Melody' scion. The second objective was to determine whether these rootstocks have different nitrogen requirements in open-field production compared with non-grafted 'Melody'. Field studies were conducted in 2013 and 2014 on the Sandhills Research Station in Jackson Springs, North Carolina. Nitrogen fertiliser was applied via drip irrigation at 0, 84, 126, 168, and 252 kg⋅ha −1 . A linear relationship between nitrogen rate and rootstock cultivar existed; however, in all cases the non-grafted plants produced more than all grafted plants. Average fruit weight from the non-grafted plants was also higher than the grafted plants. Fruit from 'Carnivor'- and 'Strongtosa'-grafted plants had higher flesh firmness compared with non-grafted 'Melody'. Our findings suggest that rootstocks do not increase yield or growth in the scion nor do they require different nitrogen application rates. However, some rootstocks do improve overall fruit quality.